THE EFFECT OF TAX SERVICE QUALITY, APPLICATION OF E-REGISTRATION AND E-FILING ON THE LEVEL OF TAXPAYER SATISFACTION OF PERSONAL PERSONS AT THE TAX SERVICE OFFICE PRATAMA MAKASSAR SELATAN - Muhammad Irfan Lukman; Tenriwaru Tenriwaru; Kirana Ikhtiari (Contemporary Journal on Business and Accounting, 2022)
Purpose – This research aims to determine the effect of quality of tax services, implementation of e-registration and e-filling on taxpayer satisfaction at KPP Pratama Makassar Selatan. Design/methodology/approach – The data collection technique used in this study is an associative approach. The data collection technique used in this study was obtained from primary data through a survey method using a questionnaire. Findings – The results of this study suggest that service quality, application of e-registration and application of e-filling have a positive and significant effect on individual taxpayer satisfaction. at KPP Pratama South Makassar. Originality – The population used in this study was from all individual taxpayers registered at KPP Pratama Makassar Selatan.